The relationship between physical, social, and personal factors and job satisfaction among work from home administrative and diplomatic officers - Abd Rahman, Shariana; Abdul Wahat, Nor Wahiza (Human Resource Management Academic Research Society, 2024)
The public sector must consider civil servants’ job satisfaction when working from home (WFH), in order to perform high-quality services. Appropriate physical, social and personal factors are needed to improve job satisfaction for employees who are working from home. This study aims to determine the relationship between physical, social, and personal factors with job satisfaction. A cross-sectional design method was used to employ a quantitative approach via self-administered questionnaire with 140 randomly selected respondents who were civil servants in Malaysia, ranked at middle-management. Results showcased significant relationship between physical, social and personal factors with job satisfaction. Further results showed that physical and social factors positively and significantly correlated with job satisfaction. There was no significant relationship between personal factors and job satisfaction. The findings of this study could serve as a guide and reference to the organizational management to improve job satisfaction of their employees who work from home.